The mucosal barrier and anti-viral immune responses can eliminate portions of the viral population during transmission and early viral growth. - Ryan V Moriarty; Athena E Golfinos; Dane D Gellerup; Hannah Schweigert; Jaffna Mathiaparanam; Alexis J Balgeman; Andrea M Weiler; Thomas C Friedrich; Brandon F Keele; Miles P Davenport; Vanessa Venturi; Shelby L O'Connor (PLoS ONE)
Little is known about how specific individual viral lineages replicating systemically during acute Human Immunodeficiency Virus or Simian Immunodeficiency Virus (HIV/SIV) infection persist into chronic infection. In this study, we use molecularly barcoded SIV (SIVmac239M) to track distinct viral lineages for 12 weeks after intravenous (IV) or intrarectal (IR) challenge in macaques. Two Mafa-A1*063+ cynomolgus macaques (Macaca fascicularis, CM) were challenged IV, and two Mamu-A1*001+ rhesus macaques (Macaca mulatta, RM) were challenged IR with 200,000 Infectious Units (IU) of SIVmac239M. We sequenced the molecular barcode of SIVmac239M from all animals over the 12 weeks of the study to characterize the diversity and persistence of virus lineages. During the first three weeks post-infection, we found ~70-560 times more unique viral lineages circulating in the animals challenged IV compared to those challenged IR, which is consistent with the hypothesis that the challenge route is the primary driver restricting the transmission of individual viral lineages. We also characterized the sequences of T cell epitopes targeted during acute SIV infection, and found that the emergence of escape variants in acutely targeted epitopes can occur on multiple virus templates simultaneously, but that elimination of some of these templates is likely a consequence of additional host factors. These data imply that virus lineages present during acute infection can still be eliminated from the systemic virus population even after initial selection.